2016
DOI: 10.1093/ntr/ntw189
|View full text |Cite
|
Sign up to set email alerts
|

Does Quitting Smoking Make a Difference Among Newly Diagnosed Head and Neck Cancer Patients?

Abstract: Introduction: To determine if smoking after a cancer diagnosis makes a difference in mortality among newly diagnosed head and neck cancer patients. Methods: Longitudinal data were collected from newly diagnosed head and neck cancer patients with a median follow-up time of 1627 days (N = 590). Mortality was censored at 8 years or September 1, 2011, whichever came first. Based on smoking status, all patients were categorized into four groups: continuing smokers, quitters, former smokers, or never-smokers. A broa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
54
1
7

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(67 citation statements)
references
References 68 publications
4
54
1
7
Order By: Relevance
“…The percentages of never, current, and former tobacco users in our study were similar to national results from past studies . In 2015, 15.1% of US adults reported being current cigarette smokers in the NHIS, whereas 17.6% of adults in this study were current cigarette smokers .…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…The percentages of never, current, and former tobacco users in our study were similar to national results from past studies . In 2015, 15.1% of US adults reported being current cigarette smokers in the NHIS, whereas 17.6% of adults in this study were current cigarette smokers .…”
Section: Discussionsupporting
confidence: 88%
“…A telephone interview study of 20,891 patients with breast cancer during 1988‐2008 reported a cigarette smoking prevalence of 20%, whereas in our study, 17.6% of breast cancer cases were current cigarette users. Past literature has reported cigarette use prevalence above the national average in patients with tobacco‐associated cancers such as lung and laryngeal cancers . A 2012 study by Park et al reported that 38.7% of patients with lung cancer had reported current smoking at diagnosis, and 90.2% were ever smokers; these figures are comparable to those for current (36.4%) and ever smokers (85.1%) among cases with tracheal, lung, or bronchus cancer in our study.…”
Section: Discussionsupporting
confidence: 77%
“…Radiation‐induced cell death is dependent on oxygen present in tumor tissues . Carbon monoxide from cigarette smoking leads to carboxyhemoglobin formation, reducing the oxygen‐carrying capacity of hemoglobin, and resulting in tissue hypoxia that hampers the ability of radiation to kill cancer cells, which is termed “hypoxic radioresistance.” Clinical studies of patients with head and neck cancer undergoing radiation who were smokers before treatment have demonstrated an association of smoking during radiation with worse survival and locoregional control . This both supports the hypoxic radioresistance theory and highlights other ill effects of cigarette smoking on tumor biology and patients' ability to tolerate treatment .…”
Section: Discussionmentioning
confidence: 63%
“…Despite abundant evidence that smoking is associated with worse outcomes for patients with cancer and strong recommendations that cessation support be integrated into cancer treatment, clinical support for smoking cessation is inconsistent. Many U.S. cancer treatment centers lack tobacco dependence treatment services and few oncologists report providing support beyond advising patients to quit .…”
Section: Discussionmentioning
confidence: 99%
“…There is a definitive link between use of tobacco products and development of oral cavity cancer (Lubin et al., ; Wyss et al., ). Moreover, people who continue to smoke after cancer treatment may experience greater cancer recurrence, poor treatment response, treatment‐related toxicity and increased cancer‐specific mortality (Choi et al., ; US Department of Health and Human Services ).…”
Section: Introductionmentioning
confidence: 99%